Méthodologie conflictuelle et protection de l'incapable étranger - Glenn, H. (Les Cahiers de droit, 1985)
The question of the law applicable to the protection of incapable foreign domiciliaries has generated much controversy in private international law. Arguments have favoured application either of the law of the foreign domicile or of the local law, yet neither solution has been consistently adopted. The author is of the view that such controversy amongst proponents of competing yet justifiable solutions is immanent in law and that both solutions must be seen as representing the private international law of incapable persons. He therefore argues in favour of a disjunctive reference of such questions to one or the other of the two laws in conflict, depending on which best serves the objective of protection of the incapable. Such a solution is incompatible with the unilateral application of the law of the forum, and notions of governmental interest or laws of « immediate application » are therefore inapplicable.